Activation energy approach for alkali-activated glass inorganic binders in different aging conditions. Issue 4 (15th April 2022) - Chen, Tai-An
Abstract : In this study, waste glass was alkali-activated by activators with different amounts of sodium hydroxide and subjected to aging. The chemical reactions and resulting microstructures and properties of the alkali-activated glass inorganic binders (AAGIBs) were affected by the aging temperature and duration. An activation energy approach was used to evaluate the effects of aging temperature and duration on the 4-day compressive strengths of the AAGIB specimens. When the amount of sodium hydroxide in the activators was low, the activation energies for the dissolution and polycondensation reactions of the AAGIBs were 83.3 kJ/mol and 44.6 kJ/mol, respectively. As the weight fraction of sodium oxide ( F SO ) in the activators was increased, the microstructure of the hardened binder was destroyed because of vigorous stirring during aging. Consequently, the activation energy of the AAGIB polycondensation reaction increased to 76.2 kJ/mol when F SO  >  5%.